Budżetowanie kosztów działań marketingowych - Kes, Zdzisław (The Budgeting of Cost of Marketing Operations, 2005)
The article describes marketing controlling in an enterprise. It is presented using the example of instruments of marketing controlling such as cost budgeting. Composing of budgets of cost requires cost identification and classification of marketing operation. Budgets of cost of marketing operations take advantage of consistent distribution with concept mix-marketing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 306-311